A case report of Mycoplasma wenyonii associated immune-mediated haemolytic anaemia in a dairy cow. Issue 1 (December 2015) - Gladden, Nicola; Haining, Hayley; Henderson, Livia; Marchesi, Francesco; Graham, Libby; McDonald, Michael; Murdoch, Fraser.; Bruguera Sala, Anna; Orr, Jayne; Ellis, Kathryn
Abstract Background and case presentation A three year old, second lactation Holstein dairy cow presented to the Scottish Centre for Production Animal Health and Food Safety, Glasgow University Veterinary School in November 2014 with a history of post-calving vulval/vaginal bleeding nine days prior to presentation, followed by a sudden reduction in milk yield. Subsequent investigations resulted in a diagnosis of immune-mediated haemolytic anaemia secondary to infection withMycoplasma wenyonii . Conclusion This report of a novel presentation ofMycoplasma wenyonii in a dairy cow illustrates the need to considerM.wenyonii as a potential differential diagnosis when a cow presents with anaemia and will discuss the potential implications of the condition at herd-level.